2016
DOI: 10.1016/j.athoracsur.2015.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter or Surgical Aortic Valve Replacement in Patients With Prior Coronary Artery Bypass Grafting

Abstract: For patients with prior coronary artery bypass graft surgery and aortic stenosis, TAVR offers a significant morbidity advantage and a strong trend toward improved survival over SAVR at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…A total of seven studies (3 randomized trials, 4 cohort) including 9221 patients (4055 in the TAVR group and 4166 in the SAVR group) were included in the analysis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Out of these, three were randomized control trials and four were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven studies (3 randomized trials, 4 cohort) including 9221 patients (4055 in the TAVR group and 4166 in the SAVR group) were included in the analysis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Out of these, three were randomized control trials and four were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The PARTNER‐2 trial showed no significant difference in mortality at 1 year between TAVR and SAVR . Whereas the CHR study showed better mortality rates with TAVR compared to SAVR . The newer generation SAPIEN XT heart valve system ( Edwards Lifesciences, Irvine, CA ) was used in the PARTNER‐ 2 trial while first generation balloon expandable SAPIEN heart valve system ( Edwards Lifesciences, Irvine, CA ) was used in the PARTNER trial; newer generation TAVR devices have been shown to have improved outcomes over the first generation devices .…”
Section: Discussionmentioning
confidence: 99%
“…The newer generation SAPIEN XT heart valve system ( Edwards Lifesciences, Irvine, CA ) was used in the PARTNER‐ 2 trial while first generation balloon expandable SAPIEN heart valve system ( Edwards Lifesciences, Irvine, CA ) was used in the PARTNER trial; newer generation TAVR devices have been shown to have improved outcomes over the first generation devices . The disparity in the results between PARTNER and CHR study can potentially be attributed to variations in baseline risk scores and differences in the number of patients developing paravalvular leak (PVL), which were lower in CHR study compared to the PARTNER trial . The severity of PVL has been directly linked to increased risk of postoperative mortality .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations